BHABANI BHATTACHARYA’S HE WHO RIDES A TIGER: A CRITICAL REVIEW (International Journal of Food and Nutritional Sciences, 2023)
Through the life history of Kalo, Bhabani Bhattacharya expresses his conviction in a positive, bright view of life. Kalo, a low-caste blacksmith upsets the social order by investing himself with Bharhminhood and rising to the top. He does not undermine the society but becomes a part of it and uses its power by accepting its rules and by fully comprehending to its purpose. He Who Rides A Tiger, written by the renowned post-independence Indian novelist Bhabani Bhattacharya, focuses on how racial and class inequality pushes a protagonist away from morality and towards vengeance. When that emotion begins to entrap him in a never-ending cycle of suffering and agony, his confession saves him and gives him the ultimate victory over himself. His writings make obvious the novelist’s worries with the social, political, economic, cultural, and spiritual issues that India was experiencing shortly after gaining independence from the British. The purpose of He Who Rides A Tiger is to show how the religion and the caste system both are false. A dramatic sequence of events demonstrates the crucial spiritual direction that emerges in times of crisis, even if one is provoked to feelings of retaliation and caught in one’s own trap.